Behaviour of Robsonella fontaniana in response to a potential predator Conducta de Robsonella fontaniana frente a un depredador potencial - Juan Francisco Ruiz; Roger D Sepúlveda; Christian M Ibáñez (Latin American Journal of Aquatic Research, 2012)
Cephalopods have two main defence strategies: the first consists on reducing the odds of being detected by a predator, while the second focuses on avoiding capture. The aim of this study was to understand the basic behavioural aspects of the octopus Robsonella fontaniana in response to the potential predator Schroederichthys chilensis (catshark) in central Chile. Experiments were conducted under laboratory conditions in order to determine the effectiveness of camouflage against predators. The results show that crypsis and an increase in the inactivity period are strategies used by octopuses as protection and defence mechanisms against predators. Los cefalópodos tienen dos estrategias de defensa principales: la primera consiste en reducir las probabilidades de ser detectados por un depredador, mientras que la segunda se centra en evitar la captura. El objetivo de este estudio fue conocer los aspectos básicos del comportamiento del pulpo Robsonella fontaniana frente al depredador potencial Schroederichthys chilensis (pintarroja). Los experimentos se realizaron bajo condiciones de laboratorio para determinar la eficacia del camuflaje para evitar al depredador. Los resultados muestran que la cripsis y un aumento del periodo de inactividad son utilizados por los pulpos como mecanismo de defensa contra los depredadores.